Factors Associated with the Incidence of Uncontrolled Hypertension in Prolanis Patients in Semarang City - Astuti, Yuni; Azam, Mahalul; Rahayu, Sri Ratna (Universitas Negeri Semarang, 2021)
Hypertension is a serious medical condition that can increase the risk of heart failure, chronic kidney disease, brain disease and others. Hypertension is a major risk factor for global death. Uncontrolled hypertension was defined as a measure of systolic blood pressure â‰¥140 mmHg and diastolic blood pressure â‰¥90 mmHg based on the mean of three measurements in hypertensive patients and with or without antihypertensive treatment. Chronic disease management (Prolanis) is a proactive and integrated program that involves participants, health facilities, especially health centers and the national health insurance called BPJS which aims to encourage patients with chronic diseases to achieve optimal quality of life. The purpose of this study was to analyze the factors associated with the incidence of uncontrolled hypertension in Prolanis patients in Semarang City. This study used case control method. The research sample consisted of 148 respondents (74 cases and 74 controls) with a purposive sampling technique. The technique of collecting data by interview using a questionnaire. Data analysis was performed using the chi-squareÂ test and logistic regression. The results showed that there was a significant relationship between the variables of age (p = 0.003), education (p = 0.032), stress (p = 0.023) and cholesterol levels (p = 0.008) with the incidence of uncontrolled hypertension in Prolanis patients in Semarang City. The most related variable was age (p = 0.028. OR = 3.469). Increasing age related to risk factors for hypertension is supported by the presence of psychological problems such as stress, can be reduced by spiritual activity and the provision of health education about changes in the cardiovascular system and adaptation to lifestyle changes will be able to reduce uncontrolled hypertension factors.